Association between varicose veins and constitution of traditional Chinese medicine plus heart-failure-like symptoms - Tsai, Cheng-Ken; Nfor, Oswald Ndi; Lu, Wen-Yu; Liaw, Yung-Po (Frontiers in Cardiovascular Medicine, 2024)
Background: Varicose veins are a common issue for employees in jobs that require prolonged standing compared with all other employees. However, its relationship with presentations of traditional Chinese medicine constitution is unknown. This study aimed to investigate their association.Material and methods: Data in the study were obtained from questionnaires of patients in Taiwan Biobank, enrolled from 2008 to 2020. The responses to the statement "I can see distorted blood vessels on my four limbs (varicose veins)." were categorized into none, mild, moderate, severe. and more severe, and the same scale was also used to classify breathing difficulties and hypotension.Results: A total of 11,293 participants were enrolled in the study. The prevalence of women was higher in the studied group compared with the control. Patients complained of breathing difficulties with moderate (30.49%) and severe discomfort (12.44%) in the diseased group. Regarding hypotension, 28.81% and 9.82% of the patients presented with moderate and severe hypotension, respectively. The cofactor odds ratio was 1.775 for severe breathing difficulty/moderate hypotension and 2.235 for severe breathing difficulty/severe hypotension, with statistical significance. The combined impact of breathing difficulties and hypotension increased with severity.Conclusions: Varicose veins had a higher association with breathing difficulties and hypotension as the severity of the condition worsened. The combined impact of breathing difficulties and hypotension increased as the disease progressed. Therefore, self-reported assessments can be a useful tool for evaluating patients with asymptomatic varicose veins before the development of 'heart-failure-like symptoms' to reduce the risk of underdiagnosis.